2017
DOI: 10.3390/geosciences8010002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Constraints and Triggering Factors of Landslides: Regional and Local Perspectives on a Drainage Basin

Abstract: Abstract:The Grande da Pipa River (GPR) basin (Portugal) has natural conditions that favor the occurrence of landslides. The hydrological year 2009/10 was characterized by high amounts of rainfall, which led to the occurrence of an also high number of landslides in this basin. The hydrodynamic character of the GPR basin was analyzed through a lumped parameter model of daily sequential water balances, in order to understand its influence in the stability of natural slopes. Results from the model were confronted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, Orejuela and Toulkeridis [ 31 ] give greater weight to precipitation in their study of susceptibility in central Ecuador. However, according to Jesus et al [ 131 ], groundwater rather than precipitation is more critical to triggering a landslide. Groundwater destabilizes the slope, reduces strength, changes density, and generates pore pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Orejuela and Toulkeridis [ 31 ] give greater weight to precipitation in their study of susceptibility in central Ecuador. However, according to Jesus et al [ 131 ], groundwater rather than precipitation is more critical to triggering a landslide. Groundwater destabilizes the slope, reduces strength, changes density, and generates pore pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the alteration of a rock mass on rock engineering parameters has been reported by Everall and Sanislav (2018) . Similarly, Jesus et al. (2018) reported that the strength of a rock formation decreases as the degree of weathering and thickness of the residual-formed soil increases.…”
Section: Introductionmentioning
confidence: 90%
“…The influence of the alteration of a rock mass on rock engineering parameters has been reported by Everall and Sanislav (2018). Similarly, Jesus et al (2018) reported that the strength of a rock formation decreases as the degree of weathering and thickness of the residual-formed soil increases. Arvanitidis et al (2019) investigated the relationship between the peak friction angle of the soil and the grain size distribution and observed that the effective peak friction angle increases as the coarse-to-fines ratio increases.…”
Section: Introductionmentioning
confidence: 90%
“…Environmental factors. A total of 12 environmental variables (factors) are used for spatial association analysis in our study, and their basic data are all available in the public domain and may be correlated with geological disasters according to previous studies [11,[43][44][45]. The Shuttle Radar Topography Mission (SRTM) and earthquake data are collected from the Land Processes Distributed Active Archive Center (https://lpdaac.usgs.gov/) and the Earthquake Disasters Program of the USGS.…”
Section: Datamentioning
confidence: 99%